A K-Means-Galactic Swarm Optimization-Based Clustering Algorithm with Otsu's Entropy for Brain Tumor Detection. Issue 2 (28th January 2019) - Nanda, Satyasai Jagannath; Gulati, Ishank; Chauhan, Rajat; Modi, Rahul; Dhaked, Uttam
ABSTRACT: Image segmentation is a technique in order to segment an image into various parts and derive meaningful information out of each one. In this article, problem of image segmentation is applied on brain MRI images. This is done in order to detect and capture the location, size and shape of five different types of tumors. Here, image segmentation is viewed as an clustering problem and a new hybrid K-means Galatic Swarm Optimization (GSO) algorithm is proposed for effective solution. The Otsus entropy measure is used as the fitness function for deriving the segments. Extensive simulation studies with five performance measures on five different brain MRI images reveal the superior performance of the proposed approach over GSO, Real Coded Genetic Algorithm (RCGA), and K-Means clustering algorithms.